Laboratory models used in the investigation of radio wave propagation in irregular structures. - Bahar, E. (IEEE Transactions on antennas and propagation)
A laboratory model first conceived by Wait (see IEEE Antennas Propagat. Mag., vol.40, p.7-24, 1998) to investigate radio wave propagation in the perturbed environment of the Earth-ionosphere waveguide is described. The construction of the laboratory model involves the exploitation of the following fundamental invariant properties of Maxwell's equations and the ability to physically simulate the appropriate boundary conditions including the Earth's curvature: (1) invariance of Maxwell's equations to size-wavelength transformations permits the scaling down in size of the Earth-ionosphere waveguide; (2) duality relationships between the electric and magnetic fields permits the representation of the azimuthally independent TMn,0 modes excited by vertical dipoles in the Earth ionosphere waveguide by the TE n,0 modes in rectangular waveguides; (3) a perfectly conducting magnetic wall (where the tangential component of the magnetic field vanishes) is simulated through the use of imaging techniques; (4) to account for dissipation in the ionosphere, an equivalent surface impedance boundary is simulated using a wall loading material with a specific thickness and complex permittivity; and (5) to simulate the Earth's curvature in the rectangular waveguide, an especially fabricated dielectric material with a prescribed permittivity height profile is used as the medium of propagation in the interior of the waveguide. All five of the above artifices have been employed in order to construct a scaled model of the Earth-ionosphere waveguide. However, one or a combination of them can be employed by researchers today to construct laboratory models from which controlled experimental data can be obtained to validate analytical and numerical solutions as well as to provide insights for novel approaches to solve difficult propagation problems